Analisis Rasio Modal Kerja Pada PT. Bank BNI Tbk - Lumantow, Laurens D.; Tampi, Dolina L.; Rogahang, Joula J. (Sam Ratulangi University, 2019)
This research aims to analyze and find out how working capital adequacy ratio. This research was conducted at the PT. Bank BNI Tbk. The methods used in this research is descriptive quantitative and analytical tools used are Working capital adequacy Ratio which consists of three types of ratios i.e. ratio of Total Assets to capital The work is clean, current liabilities against the Net working capital and working capital Turnover. The data used are secondary data from the financial statements of PT Bank BNI Tbk. Results of the study explained that the calculation of the ratio of Total Assets Against Net working capital in the year 2015 to 2017. And the results of calculation of the ratio of current liabilities against the Net working capital in the year 2015 to 2017. And the results of the calculation of working capital Turnover Ratio by the year 2015 to 2017 is also quite good. The results of the analysis of the work on capital adequacy ratio of the company will give an overview of how companies can manage the capital works. We suggest PT Bank BNI Tbk. can use working capital optimally. So the company could cover the liabilities are short-term and the company was able to produce profits every year.